Who are we receiving at the university? The impact of COVID-19 on mathematics and reading learning in high school - Ortega-Barba, Claudia Fabiola; Ramírez-Pérez, Héctor X.; Méndez-Padilla Andrade, Santiago (Frontiers in Education, 2024)
We researched how the transition to remote learning during the COVID-19 pandemic affected the development of mathematical thinking and reading comprehension skills of high school students based on the analysis of the results of a standardized test for higher education admission. The total number of participants was N = 17,942, out of which N1 = 10,611 were pre-pandemic applicants and N2 = 7,331 were post-pandemic applicants. The pre-pandemic group took into consideration the exam results from September 2016 to June 2020. The post-pandemic group took into consideration the exam results from September 2020 up to May 2023. We conclude that emergency remote teaching decreased the average mathematical competence of incoming university students by 12.8%. Similarly, emergency remote teaching decreased the average reading achievement of students entering university by 8%. Therefore, the impact of emergency remote teaching was greater on mathematics skills than on reading achievements.